(3GdJLGQI GdEdcJQhfjI (B/s - (3cGaj, gHI eUWais ((3bSfWjfI(B: s (3CdaG ddhKGFb(B, s, 2017)
(3eaGgje eQJHWI HGdJLGQI GdEdcJQhfjI (B-(3GdJLGQI GdOhdjI hOhQ GdJLGQI GdEdcJQhfjI aj GdfTGW GdGbJUGOj (B-(3GdJLGQI GdEdcJQhfjI (B-(3hSGFd GdOaY GdSOGO aj GdJLGQI GdEdcJQhfjI CHYGO (B((3LhGfH(B)(3GdJLGQI GdEdcJQhfjI GbJUGOjG(B-(3GLJeGYjG(B-(3SjGSjG (B-(3hGbY GdJLGQI GdEdcJQhfjI (B-(3YbhO GdJLGQI GdEdcJQhfjI (B-(3eNGWQ GdJLGQI GdEdcJQhfjI (B-(3Cge JWHjbGJ GdJLGQI GdEdcJQhfjI (B"(3GdJShjb GdEdcJQhfj(B".s
(3HHdjhZQGajG(B:(3U(B.295s
Keywords: (3GdJLGQI GdEdcJQhfjIs